REPRESENTATION OF MEN AS A LEADERS: DISCOURSE ANALYSIS IN USTADZ KHALID BASALAMAH'S VIDEO - Risda Aulia Wulandari (Lire Journal (Journal of Linguistics and Literature), 2020)
Media is currently changing sharply. This has encouraged various groups to utilize social media in transferring various information include transferring religion through Instagram. This opportunity makes preachers like Ustadz Khalid Basalamah use social media as a means of da'wah. The purpose of the study is to see the representation of men as leaders in the household. This research uses descriptive analysis method and uses Fairclough discourse analysis. The result of this research is the existence of the masculinity discourse which Ustadz Khalid Basalamah wishes to convey through the video he uploaded on his Instagram account